Media Pembelajaran Matematika Konkret Versus Digital: Systematic Literature Review di Era Revolusi Industri 4.0 - Gusti Firda Khairunnisa; Yuli Ismi Nahdiyah Ilmi (Jurnal Tadris Matematika, 2020)
The development of technology in the age of the fourth industrial revolution affects almost every aspect of human lives, including education sector. Therefore, learning innovations are needed in order to meet learning objectives. The objectives are coaching people who are competitive and have 4C skills (communication, collaboration, critical thinking and problem solving, creativity and innovation). One of the learning innovations in mathematics is the application of concrete and digital learning media. To explore and summarize the latest facts related to the concrete and digital mathematics learning media during industry 4.0, the authors of this study conducted a research using Systematic Literature Review method. A total of 30 literatures from various databases were interpreted. A review was drawn on the uses, strengths, and weaknesses of digital and concrete mathematics learning media during industry 4.0. The concrete learning media has advantages which include improving students’ problem solving, creative thinking, and visual thinking skills, but it requires more attention and care. Meanwhile, the advantages of digital learning media include increasing the effectiveness and efficiency of learning mathematics, supporting distance learning, and not requiring special maintenance. Nevertheless, there are still students and teachers who are not familiar with technology, some students do not have gadgets, and there are also inadequate internet networks in some areas.